Pharmacokinetics of obinutuzumab in Chinese patients with B‐cell lymphomas. (14th February 2017) - Zhai, John; Qin, Yan; Zhu, Jun; Song, Yuqin; Shen, Zhixiang; Du, Xin; Jamois, Candice; Brewster, Michael; Shi, Yuankai; Shi, Jun
Abstract : Aim: The Phase Ib GERSHWIN study (NCT01680991) assessed the pharmacokinetic (PK) profile of obinutuzumab following multiple intravenous (i.v.) doses to Chinese patients with B‐cell lymphomas, and compared findings with previous obinutuzumab PK studies in mainly Caucasian (non‐Chinese) patients. Methods: GERSHWIN was an open‐label, single‐arm intervention study. Patients aged >18 years with CD20+ relapsed/refractory chronic lymphocytic leukaemia (CLL), diffuse large B‐cell lymphoma (DLBCL) or follicular lymphoma (FL) were enrolled from four centres in China. The treatment period was 24 weeks; patients received obinutuzumab 1000 mg i.v. on Days (D)1, 8 and 15 of Cycle (C)1 (CLL patients: first infusion split over 2 days) and on D1 of C2–8 (all cycles: 21 days). PK parameters were estimated using non‐compartmental analysis (NCA), and a population PK analysis was used to determine whether observed GERSHWIN PK data were in accordance with previous obinutuzumab PK studies in non‐Chinese patients. Results: The PK analysis population included 48 patients: 28 patients completed all treatment cycles. NCA showed a similar PK profile in Chinese patients with FL, DLBCL and CLL. Steady‐state concentrations of obinutuzumab appeared to be reached at the start of C2 irrespective of histology. There was no apparent relationship between body weight and systemic exposure. Most PK profiles observed in GERSHWIN lay within the 90% prediction interval of simulated profiles. Conclusions: Obinutuzumab exposure was comparable in CLL, DLBCL and FL patients. NCA and population PK analysis indicate that PK characteristics of Chinese patients with B‐cell lymphomas are similar to those in non‐Chinese patients.